Bmi1 Is a Key Epigenetic Barrier to Direct Cardiac Reprogramming - Zhou, Yang (Cell Stem Cell, 2016)
Direct reprogramming of induced cardiomyocytes (iCMs) suffers from low efficiency and requires extensive epigenetic repatterning, although the underlying mechanisms are largely unknown. To address these issues, we screened for epigenetic regulators of iCM reprogramming and found that reducing levels of the polycomb complex gene Bmi1 significantly enhanced induction of beating iCMs from neonatal and adult mouse fibroblasts. The inhibitory role of Bmi1 in iCM reprogramming is mediated through direct interactions with regulatory regions of cardiogenic genes, rather than regulation of cell proliferation. Reduced Bmi1 expression corresponded with increased levels of the active histone mark H3K4me3 and reduced levels of repressive H2AK199ub at cardiogenic loci, and de-repression of cardiogenic gene expression during iCM conversion. Furthermore, Bmi1 deletion could substitute for Gata4 during iCM reprogramming. Thus, Bmi1 acts as a critical epigenetic barrier to iCM production. Bypassing this barrier simplifies iCM generation and increases yield, potentially streamlining iCM production for therapeutic purposes.